1994
DOI: 10.1079/bjn19940114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of zinc bioavailability: studies in rats on zinc absorption from wheat using radio- and stable isotopes

Abstract: Absorption from wheat intrinsically and extrinsically labelled with 67Zn and extrinsically labelled with 65Zn was measured from 67Zn faecal excretion and 6sZn whole-body retention in rats. There were significant differences between the extrinsically-and intrinsically-labelled 67Zn (P < 0.001), but not between the extrinsically-labelled 65Zn and intrinsically-labelled 67Zn. The effect of chicken meat on the absorption of Zn from intrinsically-labelled wheat was also studied in the rat. Mean Zn absorption from w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Published studies comparing absorption of intrinsic and extrinsic Zn isotope tracers have provided inconclusive results. Six reports of such studies in rats demonstrated either no significant difference or that the extrinsic tracer was absorbed to a greater or lesser extent (14)(15)(16)(17)(18)(19). Of 6 studies in humans, 4 found no significant difference, whereas 2 studies indicated that the extrinsic label was absorbed at a lower level (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 98%
“…Published studies comparing absorption of intrinsic and extrinsic Zn isotope tracers have provided inconclusive results. Six reports of such studies in rats demonstrated either no significant difference or that the extrinsic tracer was absorbed to a greater or lesser extent (14)(15)(16)(17)(18)(19). Of 6 studies in humans, 4 found no significant difference, whereas 2 studies indicated that the extrinsic label was absorbed at a lower level (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have been performed to validate the extrinsic labelling approach, in particular for Zn, with contradictory results. Even if it is still not certain that the isotope behaves in exactly the same way as the native Cu or Zn bound in the food matrix (Fairweather-Tait et al 1991;Fox et al 1994;Boza et al 1995), it is accepted that extrinsic labels may be used as an approximate guide when assessing the bioavailability of Cu and Zn from different regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly and almost fully absorbed (about 79 %) in upper part of the gastrointestinal tract of rats fed free compound (601) Small-intestinal phytases have high activity in rats and very much lower activity in human subjects and pigs (217) Fe: 1 -20 % in human subjects fed usual diets (204) Mg: 70 % in rats fed whole-wheat flour (219) 21 -28 % in human subjects fed brown bread diet (602) 50 % in human subjects fed a typical diet (603) 57·6 % in human subjects fed a standard diet (604) Zn: 16·6 % in human subjects consuming wholemeal bread (605) 20 % in adult women consuming whole-wheat tortillas (606) 35 % in rats fed whole-wheat flour (219) 88·9 -94·6 % in rats fed whole-wheat flour (607) 18·5 % in rats fed wheatmeal (608) 60 -82 % in rats fed whole-grain wheat (609) 30 -37 % in rats fed whole-wheat flour chapatti (610) Cu: 62 -85 % in human subjects fed whole-wheat bread (611) 16·3 -16·5 % in rats fed free compound (71,73) Se: 81·1 -84·5 % in rats fed whole-wheat flour (607) 73 -86 % in rats fed whole wheat as compared with sodium selenite (612) 100 % in rats fed whole-wheat flour as compared with sodium selenite (613) P: 41-55 % in human subjects fed brown bread diet (602) Ca: 81·7 % in human subjects fed whole-wheat bread (614) 43 -44 % in rats fed whole-wheat flour chapatti (610) 85·7 -92·8 % in rats fed whole-wheat flour (607) Thiamin (vitamin B 1 ): 91 % in rats fed whole-wheat bread compared with free thiamine mononitrate (100 %)…”
Section: Appendixmentioning
confidence: 99%